Survey of antifungal prophylaxis and fungal diagnostic tests employed in malignant haematology and haemopoietic stem cell transplantation (HSCT) in Australia and New Zealand. Issue 12 (December 2014) - van Hal, S. J.; Gilroy, N. M.; Morrissey, C. O.; Worth, L. J.; Szer, J.; Tam, C. S.; Chen, S. C.; Thursky, K. A.; Slavin, M. A.
Abstract This article reports the findings of a survey developed to assess the current use of antifungal prophylaxis among haematology and infectious disease clinicians across Australia and New Zealand, and their alignment with existing consensus guidelines for the use of antifungal agents in the haematology/oncology setting (published 2008). Surveyed clinicians largely followed the current recommendations for prophylaxis in the setting of induction chemotherapy for acute myeloid leukaemia, as well as autologous and low‐risk allogeneic haemopoietic stem cell transplantation (HSCT). In keeping with guideline recommendations, posaconazole was the agent used by most centres for high‐risk allogeneic HSCT. However, its routine continuation for 75–100 days post‐transplantation without de‐escalation suggested use beyond those indications described in the 2008 guidelines, namely pre‐engraftment neutropenia and graft‐versus‐host disease. Variations in practice were observed in other settings, such as acute lymphoblastic leukaemia and myelodysplastic syndrome, reflecting the general lack of evidence for antifungal prophylaxis in these patient populations and changing perceptions of risk. With regard to the availability of testing in cases of suspected breakthrough IFD, 40% of centres did not have access to investigative bronchoscopy within 48 h of referral, and results of Aspergillus galactomannan (GM), fungal polymerase chain reaction and therapeutic drug monitoring (TDM) were not available within 48 h in 83%, 90% and 85% of centres respectively. The survey's findings will influence the recommendations provided in the updated 2014 consensus guidelines for the use of antifungal agents in the haematology/oncology setting.